A complete clinico-epidemiological and microbiological profile of candidemia cases in a tertiary-care hospital in Western India - Ekadashi Rajni; Preeti Chaudhary; Vishnu Kumar Garg; Rajani Sharma; Manisha Malik (Cambridge University Press, 2022)
Abstract Objective: To identify different Candida spp along with antifungal susceptibility pattern and risk factors associated with candidemia. Design, setting, and patients: This retrospective observational study was conducted in a tertiary-care academic hospital in Jaipur, Western India, for 3 years (July 2017-June 2020). Methods: Blood cultures were performed according to standard microbiological methods, and only 1 isolate per patient was included in the study. Isolates of Candida spp were identified using a VITEK-2 automated system and matrix-assisted laser desorption ionization-time of flight mass spectrometry. Antifungal susceptibility tests were performed using the broth microdilution assay according to the Clinical and Laboratory Standards Institute guidelines. Results: Of 3,443 blood cultures received from suspected sepsis cases, candidemia was identified in 95 (2.8%). In addition to Candida tropicalis (n = 36; 38%) and Candida parapsilosis (n = 17; 18%), 10 isolates of Candida auris comprised the fourth most common cause of candidemia. Presence of central venous catheter and diabetes were statistically significant risk factors for development of candidemia by NAC. Resistance to fluconazole was 36%, resistance to voriconazole was 20%, resistance to 5-flucytosine was 4%, and resistance to amphotericin-B was 7%. C. auris isolates were more resistant than other NAC spp. We detected no resistance among the echinocandins. Conclusions: The emergence of highly resistant isolates like C. auris emphasizes the need for constant monitoring of candidemia cases for species identification and routine antifungal susceptibility so that appropriate measures can be taken to reduce the related morbidity and mortality.